Efektivitas Penggunaan Aplikasi Aku Pintar Dalam Asesmen Kebutuhan Siswa Di Sekolah - Ikafitri, Nur Artha; Marsuki, Nur Asky; Wahyuni B, Sri; H, Nurhikmah; Tohamba, Citra Prasiska Puspita (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2026)
The diverse needs of students require guidance and counseling teachers to conduct accurate and rapid assessments with the support of digital technology such as the Aku Pintar application, which facilitates effective data collection and analysis. This study aims to evaluate the effectiveness of the Aku Pintar application in assessing student needs in schools through a descriptive-reflective literature review. The analysis was conducted by reviewing various relevant studies and academic articles related to the implementation of digital assessment in guidance and counseling practices. The results of the study indicate that the Aku Pintar application helps guidance and counseling teachers identify students' academic and non-academic needs more quickly and accurately. Furthermore, this study synthesizes that the effectiveness of using digital applications in guidance and counseling services is determined not only by technological superiority but also by teachers' digital literacy readiness and school system support. Theoretically, this study contributes to strengthening the concepts of digital counseling and data-driven counseling in the context of student needs assessment in schools. Practically, the results of this study provide implications for guidance and counseling teachers and educational institutions to improve digital competency and provide infrastructure support to optimize the use of technology in guidance and counseling services. These findings also emphasize the importance of teachers' digital literacy readiness in utilizing assessment technology, as well as the need for continuous professional development. Keywords: Aku Pintar application; digital guidance and counselling; effectivenessstudent needs assessment;